The lesser-known medusa Drymonema dalmatinum Haeckel 1880 (Scyphozoa, Discomedusae) in the Adriatic Sea - Malej, Alenka (Annales. Series historia naturalis, 2014)
Authors report historical and recent records of the little-known medusa Drymonema dalmatinum in the Adriatic Sea. This large scyphomedusa, which may develop a bell diameter of more than 1 m, was first described in 1880 by Haeckel based on four specimens collected near the Dalmatian island Hvar. The paucity of this species records since its description confirms its rarity, however, in the last 15 years sightings of D. dalmatinum have been more frequent.
Keywords: Adriatic Sea; dalmatinska lasasta meduza; Gulf of Trieste; historični zapisi; Jadransko morje; meduze; redki klobučnjaki; Tržaški zaliv